Nilai-Nilai Ke-Islam-An Pada Budaya Robo-Robo Masyarakat Muslim Sungai Batang Kabupaten mempawah - Abdullah, Abdullah; Dizza, Primatasha Desvira (Journal of Research and Thought on Islamic Education (JRTIE), 2024)
Abstract: national treasure, with a specific focus on the Robo-Robo tradition in Sungai Batang Village, Mempawah Regency. Culture, as a product of human creativity, is passed down through generations, giving rise to living traditions that become integral parts of the local community. Islamic value education, grounded in the Quran and Hadith, plays a central role in shaping individuals with faith and noble character. The Robo-Robo tradition in Sungai Batang Village serves as a tangible example of local wisdom that is not only resistant to change but also encompasses profound Islamic values. The integration of this local wisdom across ethnicities fosters a sense of solidarity among the diverse ethnic and cultural groups in Sungai Batang Village, including the Malay, Chinese, and Madurese communities. The text highlights that the efforts to educate and preserve culture extend beyond traditional settings and permeate into the educational institutions of Sungai Batang Village. This underscores the crucial role of education in transmitting traditions to future generations. The dynamics of culture and individual adaptation are integral aspects of maintaining the Robo-Robo tradition, requiring alignment between internal and external factors to uphold harmony. Further research is suggested to delve deeper into the role of the Robo-Robo tradition concerning the local belief in potential dangers on the last Wednesday of Safar. In conclusion, this text provides an overview of the paramount importance of preserving local wisdom, particularly in the Robo-Robo tradition, as a vital component of the cultural identity of Sungai Batang Village. This identity reflects notions of solidarity, Islamic values, and ethnic diversity.